A contextual critique of critical literacy: Freirean 'generative themes' and their impact on pedagogic practice. Issue 1 (2nd January 2018) - Weninger, Csilla
ABSTRACT: Public education in post-industrial societies has been restructured based on a human capital model that prioritizes the economic value of citizens for the benefit of globally competitive national economies. In a policy-as-numbers climate [Lingard, B. (2011). Policy as numbers: Ac/counting for educational research. The Australian Educational Researcher, 38 (4), 355–382], school administrators and teachers struggle to 'produce results' and 'close gaps' within accountability systems built on standardized measures of learning. What possibilities exist for critical literacy as viable classroom pedagogy in such an environment? This article offers a contextual–empirical analysis of efforts to implement critical literacy in mainstream secondary classes in Singapore. Drawing on Freire's notion of generative themes, it identifies key political-policy constraints, showing how they impacted the pedagogical enactment of critical literacy tenets and pinpointing a focal direction for critical literacy in Singapore's English education. More generally, the article argues that critical literacy, more than ever, must be a localized practice responding to exigencies emerging at the global–local nexus.